Fabrication and characterisation of aluminium copper yitrium nickel alloy - Mohd Jeffry Radzi (School of Materials Engineering, 2016)
The purpose of this project is to study the different percentage of Copper, Nickel and Yttrium in the Aluminium based alloy. The objectives of this study are listed as: to fabricate of Al-Cu-Ni-Y alloy using casting techniques; to determine the best composition of Al-Cu-Ni-Y alloy with respect to its physical and mechanical properties, microstructural observation and also corrosion behavior; to relate the microstructure of these alloy to their physical, mechanical and corrosion properties.